Types of social orientations of young people in the system of interethnic interaction in multiethnic cities (on the example of Bishkek) - Kozhomuratova, Baktygul (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2025)
The relevance of the study of types of social identity in Bishkek is conditioned by the need to eliminate social stereotypes regarding different ethnic groups and demonstrate possible productive behaviours to avoid interethnic conflicts. The purpose of this study was to investigate the productive and unproductive types of social orientations within the multiethnic city of Bishkek. The following methods were used: the method of analysing sociological information, statistical, comparative, analytical and synthetic methods. According to the 2022 Census, Bishkek is home to many nationalities, including Kyrgyz, Russians, Uzbeks, Tatars, Dungans, Kazakhs, Turks. The primary focus of this study is on the youth aged 18– 29. This paper can be used to investigate the experience of interethnic interaction on the example of different countries of the world, to consider conflict-causing factors and stereotypes in multiethnic structures.
Keywords: conflicts; kirgiška družba; Kyrgyz society; popis prebivalstva; population census; raziskave; spori; statistical data; statistični podatki; surveys